Evaluating Healthy Vending at the American Heart Association National Center: A Pilot Study. Issue 6 (July 2019) - Yan, Stella; Pappas, Antigoni; Yuan, Meghan D.; Vafiadis, Dorothea; Carson, Jo Ann
Purpose: To determine whether a 100% healthy vending model would affect revenue, employee satisfaction, and nutrition in the workplace. Design: This study compared revenue and nutrition data pre- and post-adoption of nutrition standards from the American Heart Association's (AHA) Healthy Workplace Food and Beverage Toolkit. Employee satisfaction was measured using a survey. Setting: The AHA National Center which, over time, included 5 vending machines and a micromarket. Measures: Comparisons of monthly snack and beverage revenues; survey results assessing employee satisfaction; reduction in mean saturated fat (g) and sodium (mg) per snack sold; reduction in mean sugar (g) per beverage sold; monthly mean number of fruits, vegetable, and dairy sold. Analysis: Paired t tests were used to compare monthly revenue while t tests were used to compare nutrition information pre- and post-adoption of nutrition standards. Survey results and food group purchases were analyzed using descriptive statistics. Results: Mean monthly snack revenue increased ( P = .002). Mean monthly beverage revenue did not decrease. Most survey respondents were satisfied with the healthy vending. Mean saturated fat and sodium content per snack sold decreased ( P < .001). Mean sugar content per beverage sold decreased. The micromarket sold an average of 210 units of dairy, 85 units of fruit, and 87 units of vegetables per month. Limitations: This study was conducted at one workplace. Conclusion: Healthy vending did not decrease revenue but did decrease saturated fat and sodium per snack, decrease sugar per beverage, and provide fruits, vegetables, and fat-free/low-fat dairy. Employees were generally satisfied with healthy vending.